Flavone and Flavonol derivatives as adenosine A1/A2A receptor ligands: Structure-affinity insights - Irna Groenewald; Helena D. Janse van Rensburg; Gisella Terre'Blanche (Results in Chemistry)
Kaempferol is a flavonol with anti-inflammatory and anti-oxidant activity and has also been found in medicinal plants such as Aloe vera and Ginkgo biloba. The interaction between flavonoids and proteins has attracted much attention and is of great value in developing new drugs and determining structure-activity relationships. Flavonoids have shown promising affinity towards adenosine receptors (ARs). This study selected kaempferol as the lead, and a series of synthesised and commercially available flavonoids were investigated via in vitro radioligand binding studies to determine their adenosine A1 and A2A receptor affinity. The flavonoids were divided into flavones and flavonols to examine the influence of different positions of hydroxylation and methoxylation on AR affinity. In silico evaluations of selected compounds were also performed to investigate their physicochemical and pharmacokinetic properties. The most promising compounds were 31, 37, and 38, which showed sub-micromolar affinities towards the rat A1 subtype (rA1Ki = 0.89 μM, 0.91 μM, and 0.93 μM, respectively), and 37 acted as an antagonist towards adenosine rA1 receptors. Remarkably, it was observed that methylation on the C3 position of ring C increased A1 AR affinity and selectivity. Although only four compounds showed A2A AR affinity, it was seen that replacing the phenyl ring B with a furan ring resulted in compound 39 with the best A2A affinity of 0.25 μM. Compounds 31, 37, 38 and 39 may be considered lead-like and valuable in designing novel ligands based on in vitro and silico evaluations.